Pengembangan Usaha Kuliner Pada Masa Pandemi Covid-19 di Fudgy Brownies Lampung - Zhabhet Iskandar, Ellie; Ali Alam, Iskandar (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Business culinary alone is one growing business enough fast and have enough potential big for growing. However, with existence the current COVID-19 pandemic this, give impact for continuity a business run by Fudgy Brownies Lampung as a comer new. So from that Fudgy Brownies Lampung needs strategy development right effort for develop effort the.Purpose from study this alone is for know the development strategy effort the right culinary during the covid-19 pandemic at Fudgy Brownies Lampung and increase income and maintain the business of Fudgy Brownies Lampung during the covid-19 pandemic.Regarding the data collection process, techniques collect data used is t technique interviews , observations , and questionnaires . Method analysis used in study this is method analysis qualitative that is with use information from business owner, employees and consumers (Informant). Result of study this show that Fudgy Brownies Lampung needs another strategy in develop effort this that is with develop Lampung Fudgy Brownies product to make it interesting interest buy consumer . With method use promotions on social media such as Instagram, Facebook and also Shopee. And determine the target market you want achieved.